Influence of mineral water on the structural and functional state of the rats kidneys with metabolic sindrome - Gushcha, S.; Nasibullin, B.; Zukow, W.; Savitskyi, I.; Volyanska, V. (Journal of Education, Health and Sport, 2019)
In white rats in the setting of development of metabolic syndrome inhibition of the urinary and excretory functions of the kidney, with impaired water-ion balance (the kidneys excrete slightly hyperosmotic urine in a small amount) on the background of structural signs of dystrophies. Daily diuresis is reduced by 37% due to a decrease in glomerular filtration rate (GFR) by 22% and an increase in the percentage of tubular reabsorption (p <0.001), excretion of creatinine, urea and chloride decreased by 22%, 15% and 56%. The excretion of potassium and sodium ions increases by 14% and 38%, respectively. The daily urine is greatly delayed. Two-week internal course administration of low-mineralized sodium chloride water has a positive effect on impaired renal function: the volume of diuresis is increased by 15% by accelerating GFR by 20% and restoring the value of tubular reabsorption. Creatinine excretion is increased by 20% and urea by 32%. The excretion of potassium and sodium ions is increased by 50% and 166%, respectively. Excretion of chloride ions and urine pH is fully restored. Microscopically determined residual manifestations of dystrophic processes in the kidneys, which against the background of the recovery of processes of urination and stimulation of ion-regulating and excretory functions of the kidneys, indicates the ability of the applied sodium chloride MW to correct the structural and functional disorders of the metabolic syndrome.